Innovative Teaching Strategies in Teaching English as a Foreign Language - I G A Pt Novita Sari Paragae (English Teaching and Linguistics Journal (ETLiJ), 2023)
This study aims to explain innovative teaching strategies in teaching English as a foreign language. This research was conducted by following the stages of library research. Data was collected from accredited national and international journals and analyzed qualitatively. From the data collected, it was found that the innovative learning strategy is student-centered. In the learning process, students play an active role in building their knowledge. In addition, the implementation of innovative strategies aims to prepare students to master the skills needed in the digital and global era. Innovative learning strategies are proven to provide various benefits in the language learning process. Learning strategies often implemented in learning English as a foreign language are cooperative learning, problem-based learning, and project-based learning. In terms of assessment, innovative learning uses authentic research to ensure students can implement the knowledge gained in real situations.